Exercise induced recurrence of concussion symptoms after symptom free status. Issue 11 (25th May 2017) - O'Brien, Michael J; Pepin, Michael J; Howell, David; Meehan, William P
Abstract : Objective: Determine the proportion of athletes who have a recurrence of concussion symptoms with exercise after being symptom free at rest. Design: Prospective cohort studyProspective cohort study Setting: Sport Concussion clinic Participants: Patients diagnosed with a concussion and returned to the clinic after resuming exercise. Intervention: Assessment of risk factors Outcome measures: Our main outcome variable was recurrence of symptoms with exercise after being symptom free at rest while recovering from a sport-related concussion. Co-factors included age, gender, loss of consciousness with injury, prior concussions (diagnosed and undiagnosed), post-concussion symptom scale (PCSS) score, time until clinical presentation, and duration of symptoms. Main Results: Of the 217 patients included, 25 (12%) experienced a return of symptoms. Losing consciousness at the time of injury (aOR=0.079, 95%CI=0.003–0.563) and a longer time period between injury and clinic presentation (aOR=0.936, 95%CI=0.877–0.984) were associated with a decreased risk of symptoms recurring with exercise, while those athletes that had sustained previous undiagnosed concussions (aOR=5.036, 95%CI=1.634–16.83), and had suffered a longer duration of symptoms at rest (aOR=1.006, 95%CI=1.002–1.010) were at increased risk of symptoms recurrence with exercise. Conclusions: Relatively few athletes who are symptom free at rest after a concussion will have a recurrence of symptoms when they start exercising. The risk of symptoms recurring with exercise may be higher among those athletes who have sustained previous undiagnosed concussion and had a longer period of symptoms at re. Competing interests: None. Dr. Meehan receives royalties from ABC-Clio publishing for the book, Kids, Sports, and Concussion: A guide for coaches and parents, from Springer International for the book, Head and Neck Injuries in Young Athletes, and from Wolters Kluwer for working as an author for UpToDate. He is under contract with ABC-Clio publishing for a future book entitled, Concussions. His research is funded, in part, by the Football Players Health Study at Harvard, which is funded by the National Football League Players Association and by philanthropic support from the National Hockey League Alumni Association through the Corey C. Griffin Pro-Am Tournament. Dr. O'Brien receives royalties from Wolters Kluwer for working as an author for UpToDate and from Springer International publishing for the book, Head and Neck Injuries in Young Athletes. Dr. Howell and Mr. Pepin have nothing to disclose.